2010
DOI: 10.1021/nl1000086
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Multiplex Pathogen DNA Detection by Au Particle-on-Wire SERS Sensor

Abstract: A Au particle-on-wire system that can be used as a specific, sensitive, and multiplex DNA sensor is developed. A pattern formed by multiple Au nanowire sensors provides positional address and identification for each sensor. By using this system, multiplex sensing of target DNAs was possible in a quantitative manner with a detection limit of 10 pM. Target DNAs from reference bacteria and clinical isolates were successfully identified by this sensor system, enabling diagnostics for infectious diseases.KEYWORDS D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
271
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(272 citation statements)
references
References 43 publications
0
271
0
1
Order By: Relevance
“…Additionally, the development of portable and multiplex sensor would be feasible by using multiple kinds of aptamers and correspondingly modified NWs. [22] Experimental Section Materials: Purified DNAs were obtained from Genotech (Daejeon, Korea). The metal salts (Hg(Ac) 2 , Mg(Ac) 2 , Ca(Ac) 2 , CrCl 2 , FeCl 2 , Co(Ac) 2 , NiCl 2 , CuCl 2 , Zn(Ac) 2 , Cd(Ac) 2 , and Pb(Ac) 2 ) were purchased from Sigma-Aldrich.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the development of portable and multiplex sensor would be feasible by using multiple kinds of aptamers and correspondingly modified NWs. [22] Experimental Section Materials: Purified DNAs were obtained from Genotech (Daejeon, Korea). The metal salts (Hg(Ac) 2 , Mg(Ac) 2 , Ca(Ac) 2 , CrCl 2 , FeCl 2 , Co(Ac) 2 , NiCl 2 , CuCl 2 , Zn(Ac) 2 , Cd(Ac) 2 , and Pb(Ac) 2 ) were purchased from Sigma-Aldrich.…”
Section: Resultsmentioning
confidence: 99%
“…By profiling gene expression in peripheral blood in response to respiratory viral infection, a recent study showed that these two genes are among a set of host genes differentially expressed upon viral infection [27][28][29]. It is noteworthy that before our work, various SERSbased multiplex DNA detection techniques have been reported [30][31][32][33][34][35][36]. However, most of these techniques require multiple hybridization and/or washing steps or target sequences labeling.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] Since it was discovered in the 1970s, SERS has been proven to be a sensitive technique for the detection of chemical and biological agents. [4][5][6][7][8] To widen the application of SERS technique, a great many of noble metal structures with complex morphologies [9][10][11][12][13] and controllable period [14][15][16] were investigated. The substrates based on these noble metal structures can be divided into nanoparticles (NPs) colloidal solution and solid-phase nanostructure.…”
Section: Introductionmentioning
confidence: 99%